PENANGANAN RISIKO HUKUM PEMBIAYAAN DI BANK SYARIAH - Trisadini Prasastinah Usanti (Universitas Airlangga, 2014)
The most of the assets of syariah banks are financing. On one side it is the largest source of income. however it could be the source of the greatest business risk as well. Therefore, quality of the financing must be protected and kept feasible. The legal issue analyzed in this article is about the efforts being made by Islamic banks to handle legal risks arising from financing. The approach used is the statute approach and conceptual approach. The efforts made by syariah banks in dealing with risk law financing based on two strategies, namely the restructuring of financing or settlement of financing problem.Keywords: legal risk, financing, syariah bank.